ISOLATION, STRUCTURE ANALYSIS, AND ANTIBACTERIAL ACTIVITY OF BIFLAVONOID GB-1 FROM Garcinia tetranda Pierre - Novi Sulistyaningrum; Taslim Ersam (Pusbindiklat - LIPI, 2012)
Garcinia tetranda Pierre (Clusiaceae) was reported as source of flavonoid which has various bioactivities forhealth. Pure compound has been isolated by repeat chromatography techniques (Vacuum Column Chromatography,preparative TLC and TLC). UV, IR, 1H-NMR and 13C-NMR spectroscopic data of isolated compound (isolate)compared with the compound which was found before, and showed same as biflavonoid GB-1 data. Antibacterialassay against Salmonella typhi showed lower activity than chloramphenicol. Biflavonoid GB-1 compound foundin this study is different to the previous study, which all of compounds were classified as xanthones. Therefore,result of this study improves compound variability of Garcinia tetranda. However GB-1 is not potentially used asGram-negative antibacterial agent, especially against Salmonella typhi.